“Always at Work”: Canadian Academic Librarian Work During COVID-19 - McLay Paterson, Amy; Eva, Nicole (Partnership, 2022)
To learn about the experiences of librarians working through COVID-19, we conducted semi-structured interviews with academic librarians from across Canada on issues such as workload, collegiality, and overall satisfaction with their working conditions during the pandemic. Themes emerged around job security, workload changes (both in terms of hours worked and the type of work being done), working from home, relationships with colleagues and administrators (including the perceived speed of the institution’s pandemic response and the state of communication from or with administration), and hopes for the future. This article focuses on the semantic elements of librarian work during COVID-19 uncovered during thematic analysis, including an in-depth discussion of how academic librarians’ workload changed; a second planned article will focus on latent themes on the caring nature of library work. This study connects isolated individual situations with the overall picture of what librarians’ work looked and felt like during the COVID-19 pandemic. For library administrators, we identify the ways in which institutional support helped or hindered librarians in doing their work.